Urinary and serum soluble CD25 complements urinary soluble CD163 to detect active renal anti-neutrophil cytoplasmic autoantibody-associated vasculitis: a cohort study. Issue 2 (1st March 2018) - Dekkema, Gerjan J; Abdulahad, Wayel H; Bijma, Theo; Moran, Sarah M; Ryan, Louise; Little, Mark A; Stegeman, Coen A; Heeringa, Peter; Sanders, Jan-Stephan F
Abstract: Background: Early detection of renal involvement in anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) is of major clinical importance to allow prompt initiation of treatment and limit renal damage. Urinary soluble cluster of differentiation 163 (usCD163) has recently been identified as a potential biomarker for active renal vasculitis. However, a significant number of patients with active renal vasculitis test negative using usCD163. We therefore studied whether soluble CD25 (sCD25), a T cell activation marker, could improve the detection of renal flares in AAV. Methods: sCD25 and sCD163 levels in serum and urine were measured by enzyme-linked immunosorbent assay in 72 patients with active renal AAV, 20 with active extrarenal disease, 62 patients in remission and 18 healthy controls. Urinary and blood CD4 + T and CD4 + T effector memory (TEM) cell counts were measured in 22 patients with active renal vasculitis. Receiver operating characteristics (ROC) curves were generated and recursive partitioning was used to calculate whether usCD25 and serum soluble CD25 (ssCD25) add utility to usCD163. Results: usCD25, ssCD25 and usCD163 levels were significantly higher during active renal disease and significantly decreased after induction of remission. A combination of usCD25, usCD163 and ssCD25 outperformed all individual markers (sensitivity 84.7%, specificity 95.1%). Patients positive for sCD25 but negative for usCD163 ( n  = 10) had significantly higher C-reactive protein levels and significantly lower serum creatinine and proteinuria levels compared with the usCD163-positive patients. usCD25 correlated positively with urinary CD4 + T and CD4 + TEM cell numbers, whereas ssCD25 correlated negatively with circulating CD4 + T and CD4 + TEM cells. Conclusion: Measurement of usCD25 and ssCD25 complements usCD163 in the detection of active renal vasculitis.